ISSUES OF TRANSLATING PHRASEOLOGICAL UNITS IN LITERARY WORKS (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the translation of phraseological units in literary texts from English into Uzbek. The study addresses five principal problem categories: loss of connotation, stylistic divergence, form-meaning equivalence, absence of direct lexical equivalents, and individual translator approaches. Cultural aspects are highlighted through a comparative analysis of food-related phraseological units in English and Uzbek, with attention to their Biblical, Islamic, and ethnographic sources. The article demonstrates that successful literary translation of phraseological units requires the translator to balance linguistic competence with deep cultural awareness, and to preserve figurative meaning, emotional coloring, and artistic effect while adapting expressions to the target language and culture.
Keywords: phraseological units; literary translation; connotation; stylistic equivalence; cultural factors; food-related idioms; English-Uzbek translation.